Kekuatan Kapital-kapital Kelembagaan: Belajar dari Dua Koperasi Sukses - S Adnan, Ricardi (UI Scholars Hub, 2010)
Organizational performance has always been viewed based on physical capital, such as money or assets. This is certainly not adequate because it ignores other aspects, such as intelligence, cooperation, trust, and so forth. POPIS (physical capital, organizational capital, political capital, intellectual capital, sociocultural capital) conception offers a more comprehensive perspective on the various capital that affect organizational performance. But, in fact, among the various capital, there are some capital that is more dominant than the other capital-capital. SBW and KGJ cooperative performance clearly demonstrate the dominant role of socio-cultural capital in influencing the success of those two institutions.